Sacral plexus catheter analgesia in a patient with traumatic sacral fractures and Tarlov cysts. Issue 2 (30th September 2019) - Ireland, E.; Womack, J.; Foley, E.
Summary: We report the use of a sacral plexus catheter for continuous local anaesthetic infusion in a patient with a unilateral sacral ala fracture following a fall from a horse. Although sacral plexus blockade has been well described for lower limb surgery, an ultrasound‐guided continuous catheter technique for conservatively managed fractures has not been described. Despite appropriate oral analgesia, the patient reported severe pain, particularly in the right gluteal region, which meant she was unable to sit upright or take deep breaths. A sacral plexus catheter was inserted with ultrasound guidance and an initial bolus of 30 ml levobupivicaine 0.25% was delivered followed by infusion of 8 ml.h −1 levobupivicaine 0.125%. Daily follow‐up and assessment were provided by the acute pain team. We judged the procedure to be a success as measured by an improvement in mobilisation, deep breathing, cough and patient satisfaction.